Characterization and Analysis of User Profiles in Online Video Sharing Systems - Benevenuto, Fabrício; Pereira, Adriano; Rodrigues, Tiago; Almeida, Virgílio; Almeida, Jussara; Gonçalves, Marcos (Journal of Information and Data Management, 2010)
Recently, it has been observed an increasing popularization of video sharing environments. Part of such success is due to the change on the user perspective from content consumer to content creator, basic principle of the Web 2.0. Thus, video service providers are dealing with different challenges, such as content storage, performance and scalability of servers, personalization, and service differentiation. In this context, it is crucial to understand the characteristics of requests that arrive on these servers and the patterns of user navigation on these interactive systems. This work addresses these aspects. Through the analysis of a video service workload from UOL, the largest content provider of Latin America, we present a complete characterization of user sessions, their requests to the server, and their navigation profile. Such analyses are important not only to generate synthetic workload, but also to project and create new infra-structures to video sharing systems. Our results show that there are different users profiles and also provide a better understanding of the user access pattern on video sharing systems.